Definition of bentonitic suspensions with fractional structure the newton method usage - Чумак, Віталій Лукич; Максимюк, Марія Романівна; Комкова, Людмила Сергіївна (Eastern-European Journal of Enterprise Technologies, 2012)
The method of sedimentation analysis data processing that does not depend on the law of distribution of particles of the polydisperse system by size is developed and used it for description of functions of distribution of particles of bentonite clay